2014
DOI: 10.2337/db14-1125
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate Activates Brown Adipose Tissue in Mice

Abstract: Salsalate improves glucose intolerance and dyslipidemia in type 2 diabetes patients, but the mechanism is still unknown. The aim of the current study was to unravel the molecular mechanisms involved in these beneficial metabolic effects of salsalate by treating mice with salsalate during and after development of high-fat diet–induced obesity. We found that salsalate attenuated and reversed high-fat diet–induced weight gain, in particular fat mass accumulation, improved glucose tolerance, and lowered plasma tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 37 publications
(39 reference statements)
4
43
2
Order By: Relevance
“…The compounds recently studied include a modified version of the classic protonophore, DNP (62), which is structurally similar to salicylate (53,67). These mitochondrial uncouplers result in an increase in energy expenditure similar to that obtained when treating with salsalate/salicylate (present work and previous studies [6,10,11,14,15,[52][53][54][55][56][57][58]) and also improve markers of . Therefore, considering that mitochondrial uncouplers improve T2D and NAFLD, and increasing energy expenditure is a potent mechanism to improve T2D and NAFLD (62,63,(68)(69)(70), the present work, together with previous reports in mice and humans, is highly suggestive that salicylate-driven mitochondrial uncoupling is the primary mechanism of action explaining the improvement in T2D and NAFLD associated with salsalate treatment.…”
Section: Cihr Author Manuscriptsupporting
confidence: 84%
See 2 more Smart Citations
“…The compounds recently studied include a modified version of the classic protonophore, DNP (62), which is structurally similar to salicylate (53,67). These mitochondrial uncouplers result in an increase in energy expenditure similar to that obtained when treating with salsalate/salicylate (present work and previous studies [6,10,11,14,15,[52][53][54][55][56][57][58]) and also improve markers of . Therefore, considering that mitochondrial uncouplers improve T2D and NAFLD, and increasing energy expenditure is a potent mechanism to improve T2D and NAFLD (62,63,(68)(69)(70), the present work, together with previous reports in mice and humans, is highly suggestive that salicylate-driven mitochondrial uncoupling is the primary mechanism of action explaining the improvement in T2D and NAFLD associated with salsalate treatment.…”
Section: Cihr Author Manuscriptsupporting
confidence: 84%
“…This is the first study to suggest that salicylate-driven mitochondrial uncoupling is the primary mechanism of action to explain the host of beneficial effects associated with salicylate (11,49,50) and salsalate (6-8,14,51,52). Data from the present study and previous investigations suggest that mitochondrial uncoupling resulting from the protonophoric properties of salicylate explains the consistently observed increases in energy expenditure in murine models and human subjects treated with salicylate-based compounds (6,10,11,14,15,(52)(53)(54)(55)(56)(57)(58).Classic studies from the 1950s observed that salicylate stimulates mitochondrial uncoupling (53,59), and previous work established that mitochondrial Δψm is reduced by 1.0 mmol/L salicylate (54). Moreover, proton conductance is increased with 1.0 mmol/L salicylate treatment (present data and ref.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…UCP1 is unique to thermogenic adipocytes including brown and beige adipocytes, serving as a morphological and functional marker for these cells [3]. A few compounds have been reported to activate thermogenesis [4][5][6]. These compounds were found previously to elicit beneficial effects on metabolism and enhancing thermogenesis was discovered later as one of the mechanisms.…”
Section: Dear Editormentioning
confidence: 99%
“…Taken together, ATM induces browning during the differentiation of white adipocytes. In contrast, among the previously identified thermogenesis-activating compounds, resveratrol [4] and salsalate [5] enhance the function of BAT, while berberine mainly promotes thermogenesis in mature brown and white adipocytes [6]. ATM is a first-line malaria medicine.…”
Section: Dear Editormentioning
confidence: 99%